Management of non‐visualization following dynamic sentinel lymph node biopsy for squamous cell carcinoma of the penis. (21st December 2016) - Sahdev, Varun; Albersen, Maarten; Christodoulidou, Michelle; Parnham, Arie; Malone, Peter; Nigam, Raj; Bomanji, Jamshed; Muneer, Asif
Abstract : Objectives: To review the management and clinical outcomes of uni‐ or bilateral non‐visualization of inguinal lymph nodes during dynamic sentinel lymph node biopsy (DSNB) in patients diagnosed with penile cancer and clinically impalpable inguinal lymph nodes (cN0), and to develop an algorithm for the management of patients in which non‐visualization occurs. Patients and Methods: This is a retrospective observational study over a period of 4 years, comprising 166 patients with penile squamous cell carcinoma undergoing DSNB and followed up for a minimum of 6 months. All cases diagnosed with uni‐ or bilateral non‐visualization of sentinel nodes in this cohort were identified from a penile cancer database. The management of the inguinal lymph nodes after non‐visualization and the oncological outcomes including local and regional recurrence rates were documented. Results: Out of 166 consecutive patients undergoing DSNB, 20 patients (12%) had unilateral non‐visualization after injection of intradermal 99m Tc. Of these 20 patients, seven underwent repeat DSNB at a later date, with six having successful visualization. One patient had persistent non‐visualization and proceeded to a superficial modified inguinal lymphadenectomy (SML). None of these patients experienced recurrence at follow‐up. A further seven patients underwent modified SML with on‐table frozen‐section analysis of the lymph node packet; none of these patients were found to have micrometastatic disease in the inguinal lymph nodes, although one patient developed metastatic inguinal node disease at a later date. Six patients elected to undergo clinical surveillance and have remained disease‐free. Conclusion: Patients with impalpable inguinal lymph nodes undergoing DSNB with ≥G2 T1 disease should ideally have bilateral visualization of the sentinel lymph nodes, reflecting the drainage pattern from the primary tumour. In the present series, 12% of patients were found to have unilateral non‐visualization after DSNB. Among patients offered a repeat DSNB at a later date, localizing the sentinel node was successful in 86% of cases. Patients with favourable histological characteristics can be placed on clinical surveillance. Those with high‐risk disease can be offered a repeat DSNB procedure on the proviso that SML may be carried out if there is repeated non‐visualization. Larger cohorts are required to validate this proposed algorithm.